The Sisterhood of the Traveling Pants - Brashares, Ann (Delacorte Press, 2001)
During their first summer apart, four teenage girls, best friends since earliest childhood, stay in touch through a shared pair of secondhand jeans that magically adapts to each of their figures and affects their attitudes to their different summer experiences.